A case report of intra-myometrial pregnancy - Munshi, Sujal Atul; Munshi, Ami Sujal; Nathwani, Naimish Dineshbhai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Intra-myometrial pregnancy is one of the rarest forms of ectopic pregnancy. It was first described by Dordelien et al in 1913. In intra-myometrial pregnancy the gestational sac remains within the myometrium without any connection to the endometrial cavity, fallopian tube or round ligament.